TRADISI PIWARA’AN DALAM KONTEKS DAYAK MA’ANYAN DI JEMAAT GKE HOSANA IV PIR : Suatu Kajian Teologis dalam Rangka Kehidupan Bersama Umat Kristen di Tengah Masyarakat - afriliani, Lia; Malasinta Lantigimo, Enta; Ugak, Keloso S. (Jurnal Teologi Pambelum, 2024)
Piwara'an tradition is one of the cultures owned by the Dayak Maanyan tribe in Palu Rejo Village which is lived in the life of the GKE Hosana IV PIR congregation. This research aims to describe the description of Palu Rejo Village and the GKE Hosana IV PIR congregation, describe the description of the Piwara'an Tradition and the noble values contained in it, and reconstruct theology according to the Anthropological Model and its actualization for the GKE Hosana IV PIR congregation. This type of research is qualitative research with the methods of interview, observation, and literature study. The Piwara'an tradition has positive noble values, especially closely related to the existence of Christian families in their testimony during life together with people from various backgrounds. There are three findings in the Piwara'an Tradition, namely that Dayak Maanyan people in Palu Rejo Village want to build a family that respects culture, there is an understanding that marriage and family are part of social events in the community, and marriage and efforts to build a family have a connection with God. The Piwara'an tradition reminds that there is a close relationship between humans and others, as well as humans and God that must continue to be built.